Effect of Using Bone Spreaders on Bone Density Around Dental Implants in Sinus Floor Elevation Procedures by Transalveolar Approach - الباش زياد (Latakia University Journal -Medical Sciences Series, 2023)
Aim: The aims of research is to evaluate the effectiveness of the bone spreaders in improving bone density around dental implants in maxillary sinus floor elevation procedures. Materials and Methods: The research sample consisted of 10 patients who underwent 12 surgeries to elevate the floor of the maxillary sinus by Transalveolar approache using of the bone spreaders in conjunction with the placement of dental implants. The bone density changes were studied using cone beam computed tomography. Results: One Membrane perforation occurred once out of 15 cases, 8.33%. The implant survival rate during the follow-up period was 100%. The average of preoperative bone density was 265 HU, while the average of postoperative bone density at 6 months was 619 Hu. The average of bone density changes was 354 HU. Conclusions: The Bone Spreaders are effective for maxillary sinus floor elevation by Transalveolar approache in conjunction with the placement of dental implants by improving bone density around dental implants.